2021
DOI: 10.3390/w13040517
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Removal from Wastewater: The Potential Use of Biochar and the Key Controlling Factors

Abstract: In recent years, a large volume of literature has been published regarding the removal of phosphorus (P) from wastewater. Various sorbing materials, such as metal oxides and hydroxides, carbonates and hydroxides of calcium (Ca) and magnesium (Mg), hydrotalcite, activated carbon, anion exchange resins, industrial solid wastes and organic solid wastes, have been suggested for P removal. Many of these sorbents are expensive and/or may cause some environmental problems. In contrast, biochar, as an economical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 140 publications
1
43
0
2
Order By: Relevance
“…Chemical sorption is dependent on the type of biochar, the number and type of functional groups, and the chemical composition of the biochar, while physical sorption is related to the structure and surfaces of the biochar. A similar finding was reported by Nobaharan et al (2021). The authors reported that the biochar physical properties were affected by the P sorption from wastewater, structural properties derived from different biochar original feedstocks.…”
Section: Materials Characterizationsupporting
confidence: 84%
“…Chemical sorption is dependent on the type of biochar, the number and type of functional groups, and the chemical composition of the biochar, while physical sorption is related to the structure and surfaces of the biochar. A similar finding was reported by Nobaharan et al (2021). The authors reported that the biochar physical properties were affected by the P sorption from wastewater, structural properties derived from different biochar original feedstocks.…”
Section: Materials Characterizationsupporting
confidence: 84%
“…Once exhausted, zeolites will be removed from the column and applied to soil as conditioner. The columns with biochar do not provide for a backwash because P is mainly retained irreversibly and only slightly adsorbed, thus making the desorption not economically recommended [47]. However, when biochar is exhausted, it will be applied to soil as both slow-release fertiliser and CO 2 sink [48].…”
Section: Nutrient Recovery By Biochar and Zeolitementioning
confidence: 99%
“…On the other hand, the biochar column is not provided with a backwash system, because P is mainly irreversibly retained. When the biochar is exhausted, it will be directly applied to soil as both the CO2 sink and slow-release fertilizer [25]. This pilot plant is aimed at enhancing the state-of-the-art PHA production from urban wastewater with the use of high SRT waste activate sludge (WAS) as the substrate for VFA production [21,22].…”
Section: Marineo Wwtpmentioning
confidence: 99%
“…On the other hand, the biochar column is not provided with a backwash system, because P is mainly irreversibly retained. When the biochar is exhausted, it will be directly applied to soil as both the CO 2 sink and slow-release fertilizer [25].…”
Section: Marineo Wwtpmentioning
confidence: 99%